2020
DOI: 10.1186/s40170-020-0211-1
|View full text |Cite
|
Sign up to set email alerts
|

Common biochemical properties of metabolic genes recurrently dysregulated in tumors

Abstract: Background: Tumor initiation and progression are associated with numerous metabolic alterations. However, the biochemical drivers and constraints that contribute to metabolic gene dysregulation are unclear. Methods: Here, we present MetOncoFit, a computational model that integrates 142 metabolic features that can impact tumor fitness, including enzyme catalytic activity, pathway association, network topology, and reaction flux. MetOncoFit uses genome-scale metabolic modeling and machine-learning to quantify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…Interestingly, the kcat and differential expression connection was also useful in predicting survival, supportive of the idea of metabolic rewiring giving tumors an adaptive edge [136].…”
Section: New Tools and Ideas In Connecting Kinetics To Diseasementioning
confidence: 69%
See 1 more Smart Citation
“…Interestingly, the kcat and differential expression connection was also useful in predicting survival, supportive of the idea of metabolic rewiring giving tumors an adaptive edge [136].…”
Section: New Tools and Ideas In Connecting Kinetics To Diseasementioning
confidence: 69%
“…As systematic testing of the enzymatic activity of the myriad genetic alterations reported in TCGA is often not practical, there is a great desire to develop computational tools that predict driving versus passenger genetic alterations. For example, MetOncoFit uses metabolic modeling and machine learning to analyze TCGA data to integrate and predict the catalytic and network topological features driving the metabolic reprogramming that drives tumors [ 136 ]. Oruganty et al showed that k cat was the best predictor examined for changes in enzyme expression levels in all cancer types, with increased k cat correlating with metabolic enzyme gene up-regulation, primarily through increased copy number or increased gene expression, and decreased k cat correlating with down-regulation [ 136 ].…”
Section: Enzyme Activity In Treatment and Diagnosismentioning
confidence: 99%
“…The dysregulation of serine-type endopeptidase activity may lead to degradation of the extracellular matrix and imbalance of cellular homeostasis in cancers ( Poddar, Maurya & Saxena, 2017 ). Additionally, other functional processes such as binding, catalytic, and transportation are known to be associated with carcinogenesis ( Basten & Giles, 2013 ; Oruganty et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, machine‐learning algorithms are data‐driven. Hybrid approaches that integrate machine‐learning and mechanistic modeling [ 82,83 ] can enable us to effectively harness large‐scale metabolic and epigenomic datasets in the future.…”
Section: Next‐generation Technologies For Discovering New Metabolic–ementioning
confidence: 99%